Promoting Sustained Learning through Critical Thinking Pedagogies: A Comparative Study of Singapore and Indonesia - Mutik Nur Fadhilah; Mohamad Nurahman (IAIN Madura, 2026)
This study aims to comparatively analyze critical thinking pedagogies in Singapore and Indonesia by examining how primary school teachers within the frameworks of Teach Less, Learn More (TLLM) and the Kurikulum Merdeka design and implement instruction that deliberately directs students to think critically. The research employs a qualitative approach with a cross- national descriptive-comparative design, involving two teachers from Singapore and five teachers from Indonesia as participants. Data were collected through semi-structured interviews, classroom observations, and analysis of policy and curriculum documents, and were then analyzed using thematic analysis focusing on strategies of content reduction, the design of authentic tasks and projects, the use of higher-order questioning and argumentative discussion, as well as the facilitation of students’ metacognitive reflection. The findings indicate that both TLLM and the Kurikulum Merdeka possess strong potential to foster critical thinking skills; however, teachers in Singapore are more consistent in operationalizing these principles in classroom practice through deep, dialogic, and reflective learning, whereas teachers in Indonesia are still in a transitional phase from traditional teaching patterns toward pedagogies that are genuinely oriented toward critical thinking